Сontract education: a comparative analysis - Tavshunskyi , O. (Problems of Engineer-Pedagogical Education, 2023)
The work examines changes in the system of higher education of Ukraine during the period of independence and their impact on the formation and development of the contract form of education, its current state and prospects. The genesis of contract education in Ukraine is considered in the context of global trends regarding the popularization of higher education, diversification of sources of funding for higher education, informatization of society, introduction of the concept of lifelong learning, etc. The article aims to summarize the challenges faced by the higher education system of Ukraine, in particular those related to the contract form of education, to analyze the experience of foreign countries in solving similar issues and to propose constructive steps to get out of the difficult situation in which higher education institutions of Ukraine have found themselves in conditions of depopulation and war. In the educational sphere of Ukraine, which is dominated by state higher education institutions, the processes are typical for the state sector of the economy as a whole: a shortage of highly qualified managers, inefficient use of available resources, a non-transparent system of their distribution, lack of perspective plans for the development of the industry, insufficient statistical data, slow implementation of reforms and advanced technologies, wear and tear of the material and technical base, etc. As a result, negative processes predominate: optimization of state spending on education, reduction in the number of students and quality of education, increase in tuition fees, outflow of applicants and scientists abroad. In Ukraine, there is no proper system of financial support for those seeking education, the concept of a study loan, which was proposed in the early 2000s and was attractive on paper, turned out to be ineffective and, in the conditions of the war, was completely frozen. At the same time, in 2020, as a result of the government's implementation of the transition to an indicative price for contract education, and subsequently due to COVID and the war, the number of students who found themselves in a difficult financial situation and, therefore, were forced to get a job and/or stop studying increased. Thus, one of the main criteria for access to education in Ukraine is the level of family wealth. Among the steps to improve the situation in the field of higher education in Ukraine, proposed in the article, are the reform of the system of scholarships and loans for studies, the transition to cheaper distance learning with the formation of an open Ukrainian university, the introduction of endowment funds, etc. However, all these steps require the active participation of the state, first of all, in decision-making and in the development of a regulatory framework, since it is the state that should be the most interested participant in the educational process, which the experience of other countries confirms.